“We as Human Beings Get Farther and Farther Apart”: The Experiences of Patients With Remote Monitoring Systems - Ottenberg, Abigale L. (2013)
OBJECTIVE: To explore the experiences of patients living with an implantable cardioverter-defibrillator (ICD) who had received remote monitoring (RM). BACKGROUND: Anecdotal evidence suggests that not all patients with RM use the technology. METHODS: Focus groups of patients with an ICD who received an RM system. Transcripts reviewed using thematic analysis. RESULTS: Nine patients (3 women and 6 men; median [range] age, 73 [58–91] years) received an RM system. Patients were assigned to a group in regard to RM system use (nonusers, n=5; users, n=4). Few nonusers recalled having prior conversations about the system. Users described it as “simple” and “easy” to use. Nonusers often were unsure whether their system was correctly transmitting information. System benefits perceived by users included convenience and security. Nonusers expressed mistrust. Recommendations included early education and help lines. CONCLUSIONS: Patient adherence to RM systems can be improved by explaining perceived benefits and addressing barriers to use.